TEACHING MATHEMATICS IN ECONOMICAL INSTITUTIONS OF THE REPUBLIC OF UZBEKISTAN - Kholmo'min Abduvahobovich Nazarov (Journal Park Publishing, 2022)
I’ve heard the phrase math as a country without borders several times. Despite its prohibition, there are very good reasons for the math phrase. Mathematics has a special place in human life. Experts point out that a student who masters mathematics well will have a high level of analytical and logical thinking. It develops the ability to make quick decisions, discuss and negotiate, to do things step by step, not only in solving examples and problems, but also in different situations in life. Mathematical thinking also brings it to the level of predicting the course of events that will take place in the future, the course of events that will take place in the environment.